CALCULATION METHODOLOGY OF STRESS FIELDS ON BASIS OF MACROSCOPIC DISLOCATION MODEL AT POLYSYNTHETIC TWIN BEING FAR FROM SURFACE OF TWINNING MATERIAL - O. M. Ostrikov (Наука и техника)
A calculation methodology of stress fields at a polysynthetic twin being far from crystal surface has  been  developed in the paper.  The  methodology is based on a  dislocation  manner  in  respect  to modeling crystal twinning without thin twinning approach. As an example cleavage stresses at polysynthetic twin with twins being part of its composition and having rectilinear limits at uniform distribution of twinning dislocations on them have been calculated in the paper.